An operational procedure for Hankel type integrals - C. Nasim (International Journal of Mathematics and Mathematical Sciences)
In this paper, an operational procedure is established to evaluate Hankel type integrals. First, an operator L(θ), θ≡−xddx is constructed, which defines the integral. Then making use of some basic properties of this operator, an elementary procedure is developed for evaluating integrals for a special class of analytic functions. A few example are given to illustrate the technique.